Combined Cyclosporin A and Hypothermia Treatment Inhibits Activation of BV-2 Microglia but Induces an Inflammatory Response in an Ischemia/Reperfusion Hippocampal Slice Culture Model - Wowro, Sylvia J.; Tong, Giang; Krech, Jana; Rolfs, Nele; Berger, Felix; Schmitt, Katharina R. L. (Frontiers in Cellular Neuroscience, 2019)
Hypothermia attenuates cerebral ischemia-induced neuronal cell death associated with neuroinflammation. The calcineurin inhibitor cyclosporin A (CsA) has been shown to be neuroprotective by minimizing activation of inflammatory pathways. Therefore, we investigated whether the combination of hypothermia and treatment with CsA has neuroprotective effects in an oxygen-glucose deprivation/reperfusion (OGD/R) injury model in neuronal and BV 2 microglia monocultures, as well as in an organotypic hippocampal slice culture (OHSC). Murine primary neurons, BV 2 microglia, and OHSC were pretreated with CsA and exposed to 1 h OGD (0.2 % O2) followed by reperfusion at normothermia (37 °C) or hypothermia (33.5 °C). Cytotoxicity was measured by lactate dehydrogenase and glutamate releases. Damage-associated molecular patterns (DAMPs) high mobility group box 1 (HMGB1), heat shock protein 70 (Hsp70), and cold-inducible RNA-binding protein (CIRBP) were detected in cultured supernatant by western blot analysis. Interleukin-6 (IL 6), Interleukin-1α and -1β (IL 1α/ IL1 β), tumor necrosis factor-α (TNF α), monocyte chemotactic protein 1 (MCP1), inducible nitric oxide synthase (iNOS), glia activation factors ionized calcium-binding adapter molecule 1 (Iba1), and transforming growth factor β1 (TGF β1) gene expressions were analyzed by RT-qPCR. Exposure to OGD plus 10 µM CsA was sufficient to induce necrotic cell death and subsequent release of DAMPs in neurons but not BV 2 microglia. Moreover, OGD/R-induced secondary injury was also observed only in the neurons, which was not attenuated by cooling and no increased toxicity by CsA was observed. BV-2 microglia were not sensitive to OGD/R-induced injury but were susceptible to CsA-induced toxicity in a dose dependent manner, which was minimized by hypothermia. CsA attenuated IL 1β and Iba1 expressions in BV 2 microglia exposed to OGD/R. Hypothermia reduced IL 1β and iNOS expressions but induced TNF α and Iba1 expressions in the microglia. However, these observations did not translate to the ex vivo OHCS model, as general high expressions of most cytokines investigated were observed. Treatment with CsA has neurotoxic effects on primary neurons exposed to OGD but could inhibit BV 2 microglia activation. However, CsA and hypothermia treatment after ischemia/reperfusion injury results in cytotoxic neuroinflammation in the complex ex vivo OHSC